Ejection fraction and mortality: a nationwide register‐based cohort study of 499 153 women and men. (26th November 2020) - Stewart, Simon; Playford, David; Scalia, Gregory M.; Currie, Philip; Celermajer, David S; Prior, David; Codde, Jim; Strange, Geoff; ,
Abstract: Aims: We investigated the sex‐based risk of mortality across the spectrum of left ventricular ejection fraction (LVEF) in a large cohort of patients in Australia. Methods and results: Quantified levels of LVEF from 237 046 women (48.1%) and 256 109 men undergoing first‐time, routine echocardiography (2000–2019) were linked to 119 232 deaths (median 5.6 years of follow‐up). Overall, 17.6% of men vs. 8.3% of women had an LVEF <50%. An LVEF <40% was associated with the highest crude cardiovascular‐related and all‐cause mortality at 5 years (∼20–30% and ∼ 40–50%, respectively). Thereafter, actual cardiovascular‐related and all‐cause mortality at 5 years in both sexes steeply improved to a nadir LVEF of 65.0–69.9% (reference group). Below this LVEF level, the adjusted hazard ratio (HR) for cardiovascular‐related mortality for a LVEF of 55.0–59.9% was 1.36 [95% confidence interval (CI) 1.16–1.59; P  < 0.001] in women and 1.21 (95% CI 1.05–1.39; P  = 0.008) in men. In women, an LVEF of 60.0–64.9% was also associated with a HR 1.33 (95% CI 1.16–1.52; P  < 0.001) for cardiovascular‐related mortality. These associations were most striking in women and men aged <65 years and were replicated in those with suspected heart failure (32 403 cases aged 65.2 ± 16.1 years, 57.0% women). For pre‐existing heart failure (33 738 cases aged 67.6 ± 16.9 years, 46.5% women), the specific threshold of increased mortality was at and below 50.0–54.9%. Conclusions: Among patients investigated for suspected or established cardiovascular disease, we found clinically relevant sex‐based differences in the distribution and mortality associated with an LVEF <65.0–69.9%. Specifically, they suggest a greater risk of mortality at higher LVEF levels among women. Abstract : The observed associated risk of between left ventricular ejection fraction (LVEF, on a continuous/unit‐level basis) and probability of all‐cause mortality is presented as smoothed spline curves (age‐adjusted) for women and men separately. Shaded areas represent the 95% confidence interval (CI). Box inserts show the fully adjusted risk (hazard ratio plus 95% CI) of cardiovascular (CV)‐related mortality with a LVEF 65.0–69.9% as the reference group.